Entrepreneurial education, self-efficacy and intentions in Sub-Saharan Africa - Puni, A.; Anlesinya, A.; Korsorku, P.D.A. (African Journal of Economic and Management Studies, 2018)
Purpose The purpose of this paper is to examine the mediating role of entrepreneurial self-efficacy (ESE) in the relationship between entrepreneurship education and intention in Ghana, Africa. Design/methodology/approach In all, 357 questionnaires from final year undergraduate students at a public university in Ghana are analysed using linear multiple regression. Findings The study reveals that entrepreneurship knowledge acquisition and opportunity recognition as dimensions of entrepreneurship education positively affect entrepreneurial intention (EI) and self-efficacy. Also, ESE increases the development of EI. The results further show that ESE mediated the relationship between the two measures of entrepreneurship education and EI. Practical implications The findings imply that when students are exposed to entrepreneurship knowledge and opportunity recognition skills via entrepreneurship education, they can develop high ESE and intention to engage in venture creation. Findings therefore urge stakeholders in the education sector in Africa to formulate policy guidelines for the design and teaching of entrepreneurship education. Such policies and guidelines should emphasise more students’ acquisition of adequate knowledge in venture creation and management, and the development of skills for identifying business opportunities while instilling confidence in their abilities to become successful entrepreneurs. Originality/value The mediating role of ESE in the relationship between entrepreneurship education and intention has been under-researched globally not just in Africa. Hence, this first study to the best of the knowledge in a Sub-Saharan African context, contributes further empirical evidence by demonstrating that ESE is a central psychological mechanism that can convert entrepreneurship education into EI. Besides, the study defies some of the findings in advanced economies by indicating that a theoretical entrepreneurship education course in Africa may work differently than in advanced economies and may actually foster the development of EI unlike in advanced economies.
Keywords: Ghana; Entrepreneurship education; Sub-Saharan Africa; Entrepreneurial self-efficacy; Entrepreneurial intention; Entrepreneurship training